2018
DOI: 10.21273/hortsci12396-17
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Epilobium canum garretti (Firechalice) by Axillary Shoot Culture

Abstract: Epilobium canum subsp. garrettii (firechalice) is an herbaceous wildflower with landscape potential, but its seeds are difficult to germinate because of dormancy requirements. The objective of this study was to develop a complete micropropagation procedure for a selected accession of firechalice. Single-node stem explants from the plant were examined for their ability to establish on Murashige and Skoog (MS) medium or Woody Plant Medium (WPM). Shoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…On the other hand, Deliu et al (2013) obtained the optimum rooting efficiency for medium without auxins but supplemented with activated charcoal. Alosaimi et al (2018) also noted easy rooting of Epilobium canum garretti shoots on medium without added auxin. The noted differences may result from different plant material originating from different populations derived from different climatic zones.…”
Section: Discussionmentioning
confidence: 86%
“…On the other hand, Deliu et al (2013) obtained the optimum rooting efficiency for medium without auxins but supplemented with activated charcoal. Alosaimi et al (2018) also noted easy rooting of Epilobium canum garretti shoots on medium without added auxin. The noted differences may result from different plant material originating from different populations derived from different climatic zones.…”
Section: Discussionmentioning
confidence: 86%
“…It has been well established that the optimal type of auxin hormone for root induction differs with species or genotypes. While positive results have been reported with NAA applications for root induction in several species (Azhar et al, 2018;Naaz et al, 2019), some studies have also reported toxicity and callus formation problems resulting in unsuccessful acclimatization of plantlets (De Klerk et al, 1997;Alosaimi et al, 2018). In this study, side effects, like callus formation and non-shoot induction, were also observed in V. amurensis 'Cheongsan' following the application of NAA and these effects became worse at higher NAA concentrations.…”
Section: Evaluation Of Hormonal Effects For Culture Initiationmentioning
confidence: 99%